Pharmacokinetic Properties of Pure Xanthones in Comparison to a Mangosteen Fruit Extract in Rats - Li, Li; Han, Ah-Reum; Kinghorn, A. Douglas; Frye, Reginald F.; Derendorf, Hartmut; Butterweck, Veronika (Planta Medica, 2013)
The xanthones α-mangostin and γ-mangostin are the major bioactive compounds in Garcinia mangostana (mangosteen) fruit extracts. Previously, we reported the pharmacokinetic properties of α-mangostin in rats. The purpose of this follow-up study was to compare the pharmacokinetic characteristics of α-mangostin and γ-mangostin in rats if administered as either a pure compound or as a component of a mangosteen fruit extract. The absolute bioavailability of γ-mangostin when administered as a pure compound was determined by giving male Sprague Dawley rats 2 mg/kg γ-mangostin intravenously or 20 mg/kg orally. A 160 mg/kg aliquot of mangosteen fruit extract was administered, containing α- and γ-mangostin doses equal to 20 mg/kg and 4.5 mg/kg of each pure compound, respectively. Plasma samples were collected for both pharmacokinetic studies, and compound concentrations were measured by LC-MS/MS. The pharmacokinetic of γ-mangostin after intravenous administration followed a two-compartment body model. The half-life of the distribution phase was 2.40 min, and that of the elimination phase was 1.52 h. After oral administration, both α- and γ-mangostin underwent intensive first-pass metabolism, and both compounds were conjugated rapidly after oral administration. When given as an extract, the total absorption of α- and γ-mangostin was not increased, but the conjugation was slower, resulting in increased free (unconjugated) compound exposure when compared to pure compound administration. Since reported beneficial biological activities of mangosteen xanthones are based on the free, unconjugated compounds, food supplements containing mangosteen fruit extracts should be preferred over the administration of pure xanthones.
Keywords: Garcinia mangostana; Clusiaceae; γ-mangostin; mangosteen extract; pharmacokinetics; conjugation